Plant Manipulation by Gall-Forming Social Aphids for Waste Management - Kutsukake, Mayako; Uematsu, Keigo; Fukatsu, Takema (Frontiers in Plant Science, 2019)
Many social aphids form spectacular galls on their host plants, in which hundreds to thousands of aphids thrive for several months or even for over a year. Here, in addition to colony defense against natural enemies, waste disposal is an important task for the gall dwellers to sustain their social life. In open galls, soldier nymphs actively clean colony wastes such as honeydew droplets, cast-off skins and cadavers by pushing them with their head out of the gall opening. In the gall, the excreted honeydew is coated with aphid-derived powdery wax to form “honeydew balls”, which prevents the aphids from wetting and drowning with their own excretion. How the aphids deal with the accumulated honeydew in closed galls has been a mystery. Here, we report a novel gall cleaning mechanism: the gall inner surface absorbs and removes the liquid waste through the plant vascular system. Such a plant-mediated water-absorbing property is commonly found in aphids forming closed galls, which must have evolved at least three times independently. By contrast, the inner surface of open galls is wax-coated and water-repellent, and in some cases, the inner surface is covered with dense trichomes, which further enhance the water repellency. In conclusion, gall-forming aphids induce novel plant phenotypes to manage the waste problems by manipulating plant morphogenesis and physiology for their own sake. This review describes our recent studies on waste management strategies by gall-forming social aphids and discuss future directions of this research topic.